Effects of the West Africa Ebola Virus Disease on Health-Care Utilization – A Systematic Review - Brolin Ribacke, Kim J.; Saulnier, Dell D.; Eriksson, Anneli; von Schreeb, Johan (Frontiers in Public Health, 2016)
Significant efforts were invested in halting the recent Ebola virus disease outbreak in West Africa. Now, studies are emerging on the magnitude of the indirect health effects of the outbreak in the affected countries and the aim of this study is to systematically assess the results of these publications. The methodology for this review adhered to the Prisma guidelines for systematic reveiws. A total of 3354 articles were identified for screening and while 117 articles were read in full, 22 studies were included in the final review. Utilization of maternal health services decreased during the outbreak. The number of Caesarean sections and facility-based deliveries declined and followed a similar pattern in Guinea, Liberia and Sierra Leone. A change in the utilization of antenatal and postnatal care and family planning services was also seen, as well as a drop in utilization of children’s health services, especially in terms of vaccination coverage. In addition, the uptake of HIV/AIDS and malaria services, general hospital admissions and major surgeries decreased as well. Interestingly, it was the uptake of health service provision by the population that decreased, rather than the volume of Health service provision. Estimates from the various studies suggest that non-Ebola morbidity and mortality have increased after the onset of the outbreak in Sierra Leone, Guinea and Liberia. Reproductive, maternal and child health services was especially affected, and the decrease in facility deliveries, Caesarean sections and volume of antenatal and postnatal care visits might have significant adverse effects on maternal and newborn health. The impact of Ebola stretches far beyond Ebola cases and deaths. This review indicates that indirect health service effects are substantial and both short and long-term, and highlights the importance of support to maintain routine health service delivery and the maintenance of vaccination programs as well as preventative and curative malaria programs, both in general but especially in times of a disaster.